Comparison of the Effects of Intermittent Boluses to Simple Continuous Infusion on Patients' Global Perceived Effect in Intrathecal Therapy for Pain: A Randomized Double-Blind Crossover Study. Issue 5 (19th September 2016) - Eldabe, Sam; Duarte, Rui V.; Madzinga, Grace; Batterham, Alan M.; Brookes, Morag E.; Gulve, Ashish P.; Perruchoud, Christophe; Raphael, Jon H.; Lorenzana, David; Buchser, Eric
Abstract : Objective. Intrathecal drug delivery (ITDD) is commonly used for intractable pain management. A paucity of good-quality studies in chronic noncancer patients and concerns over increased dosages have focused interest on different modes of administration. The aim of this international multicenter randomized double-blind crossover trial was to compare the efficacy of the same daily dose of drugs administered by intermittent boluses vs simple continuous infusion. Methods. Eligible patients implanted with a programmable ITDD device were randomized to receive two weeks of either intermittent boluses or a simple continuous flow in period 1, followed by a crossover to the alternative mode of administration. The primary outcome measure was the Patients' Global Impression of Change (PGIC) scale. Results. The mean proportion of positive responders (at least "minimally improved") was 38.4% in the continuous condition vs 37.3% in the bolus (difference in proportions = 1.1%, 95% confidence interval [CI] = -21.8–24.0%, P = 0.93). The mean PGIC in the continuous condition was 3.8 vs 3.9 in the bolus (mean difference = -0.1, -0.6–0.4, P = 0.72). Exploratory analyses revealed a tendency for the mean proportion of positive responders to be higher at low vs high flow rates for both bolus and continuous administrations. Two patients were withdrawn from the study due to adverse events during the bolus phase, both with symptoms of increased pain, and one patient with additional symptoms of numbness and urinary retention. Conclusion. The mean PGIC and proportion of positive responders was not substantially different after intermittent bolus vs continuous administration.